Analysis Of The Algerian Industrial Sector: Strengths, Weaknesses, And Measures For Improvement (2008-2023) - Ladjedel, Khaled (جامعة الوادي - University of Eloued, 2024)
The Industrial policies are tangle measures typical of mixed economy countries. There are a lot of types of industrial policies contain common elements with other types of interventionist practices such as trade policy, in some cases, industrial policy involves the development of public companies‬‏. The Algerian industry has been one of the most representative experiences, their industrial sector has been increasingly cited in the past years as an example for other developing countries. In recent years the Algerian industrial sector suffers hugely from many constraints, it lacks many reforms. This article discusses the industrial sector in Algeria, its current state, and its relationship with the Algerian economy. The article highlights the strengths and weaknesses of the Algerian industrial sector and proposes strategies for its development. The first section analyzes the current state of the industrial sector in Algeria, including its major industries, technological advancements, productivity levels, and challenges. The second section explores the relationship between the industrial sector and the Algerian economy, including its contribution to GDP, employment, trade, and investment. The third section examines the weaknesses and strengths of the Algerian industrial sector and proposes strategies for its advancement.
مقال
Keywords: Industrial sector ; Industrial clusters ; Imported technology ; Industrial labor ; Technical capabilities